Anesthesia Management in Laparotomy of Gastric Perforation Peritonitis: A Case Report and Literature Review - Nuh, Yalta Hasanudin; Dita, Diah Ayu Aguspa; Wirastari, Gayatri Ghea; Sahfitri, Feni Dwika (Jurnal Ilmu Kesehatan dan Kesehatan, 2023)
Gastric perforation has the potential to induce acute peritonitis, leading to intense pain and a significant mortality risk. A female patient, aged 67, presented with symptoms of intense abdominal pain affecting all regions of the abdomen and extending to the shoulder. The pain does not alleviate with rest and is aggravated by physical activity and coughing. The Chest X-ray examination revealed the presence of cardiomegaly, characterized by an enlarged heart and aortic elongation. The Abdomen X-ray examination revealed the presence of a pneumoperitoneum. Laparotomy may be conducted in individuals with gastric perforation to identify the pneumoperitoneum's underlying aetiology. The utilization of a concurrent administration of spinal anaesthesia (SA) and general anaesthesia (GA) demonstrates the effective reduction of hemodynamic impact during pneumoperitoneum while avoiding any associated adverse effects.